Sistem Pendukung Keputusan Diagnosis Diabetes Melitus Dengan Metode Simple Additive Weight (SAW) - Billy Nur Faizi; Dede Handayani (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Diabetes mellitus (DM) is a chronic lifelong disease that has a negative impact on human quality of life and increases healthcare costs. However, public awareness of the impact of DM is still low, and many people are unaware of the risk of this disease. Diabetes mellitus occurs due to the body's reduced responsiveness to insulin or the influence of other hormones that inhibit insulin production, resulting in the body's inability to control blood sugar levels. The high number of diabetes patients is caused by delays in diagnosing the disease, often leading to patient deaths from complications before being diagnosed. To address this issue, the development of a web-based decision support system using the Simple Additive Weighting (SAW) method is necessary to assist in the diagnosis of diabetes mellitus. This system is capable of selecting diagnosis alternatives after determining specific attribute weights. This research is focused on the community in Kp. Kademangan, Kec. Kelapa Dua, Kab. Tangerang, Banten, which faces the issue of insufficient accuracy in information regarding the types of diabetes mellitus experienced by the population. In this paper proposal, the author proposes the "Decision Support System for the Diagnosis of Diabetes Mellitus using the Simple Additive Weighting (SAW) Method" to address this problem.